2008
DOI: 10.1002/jae.1016
|View full text |Cite
|
Sign up to set email alerts
|

R&D and subsidies at the firm level: an application of parametric and semiparametric two‐step selection models

Abstract: Die Discussion Papers dienen einer möglichst schnellen Verbreitung von neueren Forschungsarbeiten des ZEW. Die Beiträge liegen in alleiniger Verantwortung der Autoren und stellen nicht notwendigerweise die Meinung des ZEW dar.Discussion Papers are intended to make results of ZEW research promptly available to other economists in order to encourage discussion and suggestions for revisions. The authors are solely responsible for the contents which do not necessarily represent the opinion of the ZEW.Download this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
195
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(215 citation statements)
references
References 39 publications
8
195
0
12
Order By: Relevance
“…2 Many authors have reported that R&D subsidies stimulate private investments (e.g. Almus and Czarnitzki, 2003;Hyytinen and Toivanen, 2005;Czarnitzki, 2006;Görg and Strobl, 2007;Özçelik and Taymaz, 2008;Aerts and Schmidt, 2008;Hussinger, 2008;Meuleman and Maeseneire, 2012;Czarnitzki and Lopes-Bento, 2013), but studies have also found that these funds partly or fully crowd out some private investments (e.g. Wallsten, 2000;Lach, 2002;Busom, 2000;González and Pazó, 2008;Gelabert et al, 2009 Bronzini andIachini, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Many authors have reported that R&D subsidies stimulate private investments (e.g. Almus and Czarnitzki, 2003;Hyytinen and Toivanen, 2005;Czarnitzki, 2006;Görg and Strobl, 2007;Özçelik and Taymaz, 2008;Aerts and Schmidt, 2008;Hussinger, 2008;Meuleman and Maeseneire, 2012;Czarnitzki and Lopes-Bento, 2013), but studies have also found that these funds partly or fully crowd out some private investments (e.g. Wallsten, 2000;Lach, 2002;Busom, 2000;González and Pazó, 2008;Gelabert et al, 2009 Bronzini andIachini, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These variables (combined with other matching variables) are important for minimising the selection problem concerning firm-specific R&D variables (e.g. Hussinger, 2008). Our other control variables include firm age (age and age squared) and size (number of employees and turnover) because firm innovativeness is known to be related to these factors (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, investigations of the effectiveness of prior subsidies on R&D expenditures are still scarce. For German manufacturing firms, Hussinger (2008) confirms additionality and Aschhof (2009) finds additionality for frequent recipients but neutrality for first-time receivers.…”
Section: Prior Studiesmentioning
confidence: 88%
“…The wealth of information provided by the PITEC allows an exhaustive set of variables to be selected and similar controls to be included as those used in previous evaluation studies (see, among others, Aerts and Schmidt, 2008;Almus and Czarnitzki, 2003;Antonelli and Crespi, 2013;Czarnitzki and Lopes-Bento, 2013;Czarnitzki and LopesBento, 2014;González and Pazó, 2008;Hussinger, 2008).…”
Section: Methodsologymentioning
confidence: 99%